Theoretical Study for the Calculation of Proton Range in Human Body Tissues - Hadi, Shaima M.; Saied, Bashair M. (Iraqi Journal of Science, 2021)
The main rationale for using charged particles in radiation therapy is the strong rise of energy loss (deposited dose) with maximum penetration depth ( Bragg peak) and rapid dose deposited behind the peak. Thus, a large dose can be applied to a deep seated tumor, with saving the surrounding normal tissues . Proton radiotherapy is nowadays an established method in the management of cancer diseases, although its availability is still limited to a few specialized centers. In this study, the range and the stopping power for proton interaction in the skeleton and intestine tissues, for an energy range from 0.01 to 300 MeV, was studied. The numerical calculations and analyses of Bethe Ziegler, along with CASP and SRIM software programs, were applied using Matlab program. The absorbed dose and the Bragg peak were calculated and presented as tables and figures .